Anti-freezing agent for concrete and preparation method thereof
Through the synergistic design of composite salts, porous carriers, and coating materials, the problems of low melting efficiency, poor slow-release performance, and insufficient corrosion resistance of concrete anti-icing agents in cold environments have been solved. This has achieved efficient melting, long-term slow release, and enhanced adhesion, making it suitable for concrete substrates of different strength grades.
Patent Information
- Application Number
- CN202510975402.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-11-04
AI Technical Summary
Existing concrete anti-icing agents have low melting efficiency, poor slow-release performance, insufficient corrosion resistance, and weak adhesion to the concrete matrix in extremely cold environments, and cannot meet the long-term service requirements of harsh scenarios.
A eutectic system is formed by combining calcium magnesium acetate and sodium chloride, a composite salt. This system is combined with porous carriers such as zeolite powder and coating materials such as sodium methylsilicate and phenolic resin. A hydrophobic film is formed through physical adsorption and chemical bonding, which works synergistically to improve freezing point inhibition, slow release and corrosion resistance.
It significantly improves the freezing point inhibition effect, prolongs the slow-release period, reduces the chloride ion migration rate, enhances the bond strength with concrete, improves the freeze-thaw resistance and service life of concrete, and reduces raw material costs.
Smart Images

Figure CN120888274A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of building materials, and particularly relates to an anti-icing agent for concrete and a preparation method thereof. BACKGROUND
[0002] In cold regions, the icing phenomenon on the surface of concrete structures can lead to a decrease in the anti-skid performance of the pavement and the frost heaving damage of the components, seriously threatening the traffic safety and the service life of the structures. At present, the anti-icing agent for concrete mainly plays a role by reducing the freezing point of the surface and inhibiting the formation of ice crystals. In the traditional technology, single inorganic salt has become the main component in the early stage due to its low cost and direct ice melting effect, but such a substance can easily lead to the corrosion of steel bars and the deterioration of the durability of concrete. In order to improve this problem, the existing technology inhibits the corrosion of chloride ions by adding an inhibitor or realizes the slow release of salt by using a porous material as a carrier, and some schemes further introduce an organic coating material to delay the release rate of salt. In addition, the application of organic polymers can enhance the interfacial bonding between the anti-icing agent and the concrete and reduce the loss in the freeze-thaw cycle.
[0003] However, the existing technology still has the following significant defects:
[0004] Insufficient freezing point inhibition and synergistic effect: the freezing point reduction ability of single salt or simple compound system is limited (usually only about-15℃), the ice melting efficiency is significantly reduced in the high-cold environment below-20℃, and there is no inhibition of ion synergistic effect on the growth of ice crystals, so the ice layer is easy to freeze repeatedly;
[0005] Poor slow-release performance and long-term stability: the activation treatment process (such as the temperature and time parameters are not clear) of the traditional porous carrier cannot fully develop the pore structure, the salt loading capacity is low and the release rate is uncontrollable, the effective period is generally less than 1 year, and frequent construction supplement is required;
[0006] Limited corrosion resistance and durability improvement: single coating material cannot simultaneously consider the functions of hydrophobic slow release and ion chelation, the Cl- migration inhibition rate is less than 30%, the carbonation depth of concrete is still rapidly increased in the high-humidity environment, and the long-term service requirement in harsh scenes such as cross-sea bridges and high-cold regions cannot be met;
[0007] Insufficient interfacial adhesion and process adaptability: the grafting rate and molecular weight control of organic polymers lack precise design, resulting in weak chemical bonding with the concrete matrix, and the anti-icing agent shedding rate is as high as more than 40% after the freeze-thaw cycle; at the same time, the traditional high-temperature preparation process (such as drying at >200℃) can easily damage the crystal structure of salt and the performance of polymer, and the energy consumption is high. SUMMARY
[0008] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present application provide an anti-freezing agent for concrete and a preparation method thereof, which solve the problems of insufficient freezing point inhibition, poor slow release, poor corrosion resistance and poor adhesion of the existing anti-freezing agent for concrete.
[0009] To achieve the above object, the present application provides the following technical solutions.
[0010] An anti-freezing agent for concrete comprises the following components in parts by mass:
[0011] The composite salt is 10-30 parts, which is composed of calcium magnesium acetate and sodium chloride in a mass ratio of 1:0.5-1.5;
[0012] The porous carrier is 5-15 parts, which is zeolite powder activated at 120-150 DEG C, and has a specific surface area of 300-600 m 2 / g and an average pore size of 2-5 nm;
[0013] The coating material is 1-3 parts, which is formed by radical polymerization of sodium methyl silicate and phenolic resin in a mass ratio of 1:0.5-1.0, has a grafting rate of 30%-50% and a contact angle of the coating layer of greater than or equal to 110 DEG;
[0014] The composite salt reduces the freezing point to below -25 DEG C through the eutectic effect, the porous carrier fixes the composite salt through physical adsorption, and the coating material forms a hydrophobic film layer through chemical bonding, so that the Cl- migration rate is reduced by more than 60% and the slow release effective period is up to 3 years.
[0015] Preferably, the mass ratio of calcium magnesium acetate to sodium chloride in the composite salt is 1:1, at which the freezing point is reduced to -28 DEG C and the ice melting rate is increased by 40% compared with a single salt.
[0016] Preferably, the porous carrier further comprises diatomite or volcanic ash activated at high temperature, and has a specific surface area of 200-600 m 2 / g, and when mixed with the zeolite powder, the total mass accounts for 30%-50% of the porous carrier.
[0017] Preferably, the grafting rate of sodium methyl silicate in the coating material is in the range of 30%-50% as detected by infrared spectroscopy, corresponding to a film layer thickness of 50-100 nm, which effectively inhibits the migration of the salt in the pores of the concrete.
[0018] Preferably, a preparation method of an anti-freezing agent for concrete comprises the following steps:
[0019] Step 1: drying the zeolite powder at 120-150 DEG C for 4-6 hours to activate the pore structure thereof;
[0020] Step 2: Dissolve calcium magnesium acetate and sodium chloride in deionized water in a certain proportion to prepare a supersaturated solution, and mix and adsorb the activated zeolite powder under a vacuum degree of 0.08-0.1 MPa for 2-3 hours, and then dry to obtain a salt-containing carrier;
[0021] Step 3: Dissolve sodium methyl silicate and phenolic resin in ethanol, add initiator ammonium persulfate (0.5-1% of the mass of the monomer), and perform free radical polymerization at 60-80°C for 1-2 hours to form a coating precursor solution;
[0022] Step 4: Disperse the salt-containing carrier in the coating precursor solution, and form surface-coated anti-icing agent particles by spray drying (atomization pressure 10-15 MPa).
[0023] Preferably, the temperature of the vacuum adsorption process in step 2 is controlled at 40-50°C to enhance the penetration depth of the composite salt in the pores of the zeolite powder.
[0024] Preferably, the inlet air temperature of the spray drying in step 4 is 180-200°C, and the outlet air temperature is 80-100°C, to ensure the uniformity and stability of the coating layer.
[0025] Preferably, the free radical polymerization in step 3 is carried out under nitrogen protection to avoid oxidation side reactions affecting the performance of the coating material.
[0026] Preferably, the thickness of the coating layer is 50-100 nm detected by scanning electron microscopy (SEM), and the silicon content in the coating layer is 15%-20% detected by energy dispersive spectroscopy (EDS), corresponding to a grafting density of sodium methyl silicate ≥0.8 molecules / nm 2 .
[0027] Preferably, the activation degree of the zeolite powder in step 1 is determined by nitrogen adsorption method, and the micropore volume after activation accounts for 60%-80% of the total pore volume, ensuring that the effective loading amount of the composite salt is ≥35% (mass fraction).
[0028] The technical effects and advantages of the anti-icing agent for concrete and the preparation method thereof are as follows:
[0029] 1. The invention uses calcium magnesium acetate and sodium chloride in a specific ratio (1:0.5-1:1.5) to form a eutectic system, which utilizes the interaction between ions to destroy the regularity of ice crystal growth, reduces the freezing point of the solution to below -25°C, and reduces the freezing point by more than 7°C compared to single salt. This synergistic mechanism forms a continuous ice melting environment on the surface of concrete, avoiding ice layer adhesion and freeze-thaw cycle damage, and increasing the ice melting efficiency by more than 40% compared to traditional single salt systems, effectively dealing with high-cold environments below -20°C.
[0030] 2、The invention, the porous carrier (specific surface area 300-600 m 2 / g, average pore size 2-5 nm) of zeolite powder, diatomite, etc. activated by high temperature is loaded with composite salts by physical adsorption and microporous embedding double action to form an "adsorption-slow release" structure. The salts are slowly released in the pores of the concrete by osmotic pressure and capillary action, avoiding short-term massive loss, prolonging the effective period of anti-freezing ice to more than 2.5 years, and increasing by 1-2 times compared with the direct salt mixing method without the carrier, thereby reducing the frequent construction and maintenance costs.
[0031] 3、The invention, the coated material (contact angle ≥ 110°) formed by compounding sodium methyl silicate and phenolic resin constructs a hydrophobic film layer on the surface of the carrier, which on the one hand slows down the release rate of the salts through the physical barrier to make the slow release process more uniform and controllable, and on the other hand inhibits the migration of corrosive ions such as Cl- through chemical chelation to reduce the risk of electrochemical corrosion of the steel. Compared with the uncoated system, the migration rate of Cl- is reduced by more than 50%, the carbonation depth of the concrete is reduced by 40%, and the service life of the structure in a high-salt and humid environment is significantly improved.
[0032] 4、The invention, the graft copolymer (grafting rate 30%-50%) of polyvinyl alcohol and hydroxyethyl acrylate forms a chemical bond with the concrete surface Ca 2+ through the hydroxyl groups on the molecular chain, thereby enhancing the interfacial adhesion between the anti-freezing agent and the cement matrix. This effect effectively reduces the loss of the anti-freezing agent in the freeze-thaw cycle, so that the compressive strength loss rate of the concrete is less than 1.5% after 200 freeze-thaw cycles, and the frost resistance grade is above F200, which is much better than the traditional formula without adding polymers.
[0033] 5、The invention, the preparation process uses low-temperature immersion at 60-70°C, nitrogen protection coating at 80-90°C, and spray drying at 180-200°C, etc. to avoid the damage of high temperature to the chemical structure of the salts and the performance of the polymers, thereby ensuring that the anti-freezing agent still maintains high ice-melting capacity in a low-temperature environment (the ice-melting rate is increased by 40% at -20°C). At the same time, the process energy consumption is reduced by 30% compared with the traditional high-temperature preparation method, which has both industrial production feasibility and environmental protection advantages.
[0034] 6、The invention, by adjusting the ratio of composite salts (1:0.5-1:1.5), the type of carrier (single / mixed porous materials), and the ratio of coated materials, different substrates such as C30-C60 strength grade commercial concrete, precast concrete, etc. can be flexibly adapted to different substrates, and excellent anti-freezing, freeze-thaw resistance, and corrosion resistance performance can be achieved in scenes such as airport runways, bridge expansion joints, and highways. Compared with the prior art, the invention not only achieves performance breakthrough, but also reduces the amount of single salt through component synergy, thereby reducing the raw material cost by 15%-20%, which has significant economic and social benefits. BRIEF DESCRIPTION OF DRAWINGS
[0035] Figure 1 is a method flow diagram of a concrete anti-icing agent and a preparation method thereof provided by the present application. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, and not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative labor fall within the protection scope of the present application.
[0037] It should be noted that, in this paper, relationship terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between the entities or operations, and the term "include", "contain" or any other variant is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed or inherent to such process, method, article or equipment, without more limitation, the elements defined by the statement "include" do not exclude the presence of other identical elements in the process, method, article or equipment including the elements,
[0038] Reference Figure 1 The present application provides an anti-icing agent for concrete and a preparation method thereof, and the specific implementation mode of the detailed description system in the coal mine scene. Each embodiment is expanded according to the implementation purpose, system composition, implementation steps, and implementation effect, ensuring the landability and verifiability of the technical solution, and fully supporting the precise positioning, pedestrian identification and safety warning function of the trackless rubber-tyred vehicle in the coal mine.
[0039] Embodiment 1
[0040] Reference Figure 1 The embodiment provides an anti-icing agent for concrete and a preparation method thereof, which is used for the implementation of the anti-icing agent with a composite salt ratio of 1:1, and the specific implementation content includes:
[0041] Implementation components (mass parts):
[0042] Calcium magnesium acetate (10 parts) and sodium chloride (10 parts) are compounded (ratio 1:1);
[0043] Zeolite powder (10 parts) is activated at 130°C for 4 hours, and the specific surface area is 450m 2 / g, and the average pore size is 3nm;
[0044] Coating material (2 parts): sodium methylsiliconate and phenolic resin mixed at 1:0.8, grafting rate 40%, film thickness 70 nm.
[0045] Implementation steps:
[0046] Carrier activation: zeolite powder dried at 130°C for 4 hours, porosity increased to 65%.
[0047] Salt adsorption: composite salt dissolved in deionized water to form a supersaturated solution, adsorbed with zeolite powder at a vacuum degree of 0.09 MPa and 45°C for 2.5 hours, and the salt content after drying reached 40%.
[0048] Coating polymerization: sodium methylsiliconate and phenolic resin were polymerized at 60°C under nitrogen protection for 1.5 hours, and then spray dried (atomization pressure 12 MPa, inlet temperature 190°C) after adding the salt-containing carrier, forming a hydrophobic film layer with a contact angle of 115°.
[0049] Performance test:
[0050] Freezing point: -28°C (13°C lower than single salt).
[0051] Slow-release validity period: 3.2 years (detected by conductivity method, and the Cl- release amount in the third year still reached 70% of the initial value).
[0052] Cl- migration rate: 0.08 x 10-12 m 2 / s (62% lower than the uncoated sample).
[0053] Ice melting rate: 0.8 g / cm 2 ·h (45% higher than the traditional formula).
[0054] Example 2
[0055] This example provides an anti-icing agent for concrete and a preparation method thereof, which is used in the implementation of an anti-icing agent with a composite salt ratio of 1:0.5, and the specific implementation content includes:
[0056] Components (mass parts):
[0057] Calcium magnesium acetate (15 parts) and sodium chloride (7.5 parts) are compounded (ratio 1:0.5);
[0058] Diatomite (15 parts) activated at 120°C for 6 hours, specific surface area 300 m 2 / g, average pore size 2 nm;
[0059] Coating material (1.5 parts): sodium methylsiliconate and phenolic resin mixed at 1:0.5, grafting rate 30%, film thickness 50 nm.
[0060] Implementation steps:
[0061] Carrier activation: diatomite was dried in 120℃ oven for 6 hours to remove adsorbed water and activate the microporous structure. The specific surface area was 300 m 2 / g and the micropore volume was 65% of the total pore volume.
[0062] Composite salt adsorption: calcium magnesium acetate and sodium chloride were dissolved in deionized water at 70℃ to prepare a supersaturated solution (solubility 85 g / 100 mL) and mixed with activated diatomite at a mass ratio of 1:3.
[0063] Adsorption was carried out in a 40℃ water bath under vacuum of 0.08 MPa for 3 hours (lower than 45℃ in Example 1 to avoid early precipitation of low proportion of sodium chloride), and the salt loading was measured to be 32% (mass fraction) after drying.
[0064] Coating precursor solution preparation: sodium methylsilicate and phenolic resin were dissolved in anhydrous ethanol at a ratio of 1:0.5, and 0.5% ammonium persulfate of monomer mass was added as an initiator. The mixture was stirred in a 60℃ oil bath for 1 hour. Infrared spectroscopy showed a grafting rate of 30% (decrease in -OH peak intensity and increase in Si-O-C peak intensity).
[0065] Spray drying coating: salt-containing diatomite was dispersed in the coating solution, and a pressure-type spray dryer (atomization pressure 10 MPa, inlet air temperature 180℃, outlet air temperature 80℃) was used to form uniform particles with a film thickness of 50 nm. The contact angle was measured to be 110°.
[0066] Performance test:
[0067] Freezing point: -25℃ (satisfies the lower limit of claim 1).
[0068] Slow-release effective period: 2.8 years (Cl- release amount reached 75% of the initial value in the second year).
[0069] Cl- migration rate: 0.12 x 10-12 m 2 / s (50% lower than the comparative example).
[0070] Carbonation depth: in the simulation environment of the cross-sea bridge, the carbonation depth was only 1.2 mm after 56 days (40% reduction).
[0071] Example 3
[0072] This example provides an anti-freezing agent for concrete and a preparation method thereof, which is used for the implementation of an anti-freezing agent with a composite salt ratio of 1:1.5. The specific implementation content includes:
[0073] Components (mass parts):
[0074] Calcium magnesium acetate (8 parts) and sodium chloride (12 parts) were compounded (ratio 1:1.5).
[0075] Volcanic ash (12 parts) was activated at 150 °C for 3 hours, and the specific surface area was 600 m 2 / g, and the average pore size was 5 nm.
[0076] Coating material (3 parts): sodium methyl silicate and phenolic resin were mixed at a ratio of 1:1, the grafting rate was 50%, and the film thickness was 100 nm.
[0077] Implementation steps:
[0078] Carrier activation: the volcanic ash was calcined in a muffle furnace at 150 °C for 3 hours (short-time high temperature promotes pore expansion), and after activation, the specific surface area was 600 m 2 / g, and the average pore size was 5 nm, and the micropore volume accounted for 70%.
[0079] Composite salt adsorption: dissolve the salts at a ratio of 1:1.5, prepare a supersaturated solution at 80 °C (solubility 92 g / 100 mL), and mix with the volcanic ash at a mass ratio of 1:4, adsorb at a vacuum degree of 0.1 MPa and a temperature of 50 °C for 2 hours (high temperature accelerates ion diffusion), and after drying, the salt loading reaches 38% (mass fraction).
[0080] Coating precursor solution preparation: increase the phenolic resin ratio to 1:1, add 1% ammonium persulfate of the monomer mass, and polymerize under nitrogen protection at 80 °C for 2 hours (extend the reaction time to improve the grafting rate), infrared spectroscopy shows that the grafting rate is 50%, and SEM observation shows that the film thickness is 100 nm.
[0081] Spray drying coating: increase the atomization pressure to 15 MPa (high pressure ensures uniform atomization of high-viscosity coating liquid), the inlet air temperature is 200 °C, and the outlet air temperature is 100 °C, forming a dense film layer with a contact angle of 118°, and EDS detects that the silicon content is 20%.
[0082] Performance test:
[0083] Freezing point: -26 °C (11 °C lower than single salt).
[0084] Slow-release effective period: 2.5 years (the Cl- release amount in the second year reaches 65% of the initial value).
[0085] Heavy metal content: Pb 0.005%, Cd 0.003% (complying with GB / T31886-2015 standard).
[0086] Example 4
[0087] The embodiment provides an anti-freezing agent for concrete and a preparation method thereof, and the specific implementation content includes:
[0088] Components (mass parts):
[0089] Composite salt (15 parts, ratio 1:1);
[0090] Zeolite powder (7 parts) + diatomite (3 parts) mixed carrier (total 10 parts), activated at 130℃ for 4 hours;
[0091] Coating material (2 parts): sodium methyl silicate mixed with phenolic resin at a ratio of 1:0.8, with a grafting rate of 40%.
[0092] Implementation steps:
[0093] Carrier pretreatment: zeolite powder (activated at 130℃ for 4 hours) and diatomite (activated at 120℃ for 6 hours) are physically mixed at a ratio of 7:3, and the specific surface area of the mixed carrier is measured to be 420 m 2 / g, with a pore size distribution of 2-5 nm accounting for 85%.
[0094] Composite salt adsorption: using the vacuum adsorption conditions of Example 1 (0.09 MPa, 45℃, 2.5 hours), the salts are adsorbed in different pore sizes of the mixed carrier, with the zeolite powder large pores (3-5 nm) mainly loading the salts and the diatomite micropores (2-3 nm) achieving fine embedding, with a loading capacity of up to 36% (mass fraction).
[0095] Coating and drying: the coating liquid formulation and spraying parameters of Example 1 are used (atomizing pressure 12 MPa, inlet air temperature 190℃), SEM shows that the film layer uniformly covers the two carrier particles, EDS detects uniform distribution of silicon elements at the interface, proving the compatibility of the mixed carrier and the coating layer.
[0096] Performance test:
[0097] Specific surface area: 420 m 2 / g (mixed carrier adsorption capacity increased by 15%).
[0098] Slow-release stability: after 100 cycles at -20℃, the Cl- release rate only decreases by 10% (25% for single carrier).
[0099] Infrared spectrum verification: the grafting rate of the coating material is confirmed by the peak shift of 2920 cm -1 (C-H stretching) and 1080 cm -1 (Si-O-C stretching).
[0100] Example 5
[0101] This example provides an anti-freezing agent for concrete and a preparation method thereof, which is used for high-cold region application examples, and the specific implementation content includes:
[0102] Concrete proportioning:
[0103] C50 concrete: cement 450 kg / m3 sand 650 kg / m 3 gravel 1100 kg / m 3 water 180 kg / m 3 deicing agent (Example 1 formulation) 3%.
[0104] Implementation steps:
[0105] Deicing agent preparation:
[0106] The 4-step process of Example 1 was followed exactly to produce particles with an average particle size of 50-100 μm. SEM / EDS analysis showed a film thickness of 70 nm, a silicon content of 18%, and a salt loading of 40%.
[0107] Concrete mixing:
[0108] The concrete was mixed according to the C50 concrete formulation (cement 450 kg / m 3 , sand 650 kg / m 3 , gravel 1100 kg / m 3 , water 180 kg / m 3 ). The deicing agent was added to the mixer at 3% of the mass of the cementitious material (13.5 kg / m 3 ).
[0109] The cement, sand, and gravel were dry mixed for 30 seconds, then the deicing agent and water were added and wet mixed for 2 minutes to ensure uniform dispersion of the particles. The slump of the fresh concrete was controlled to 180 ± 20 mm.
[0110] Application results:
[0111] Freeze point depression: In an environment of -25°C, the ice layer on the surface of the concrete completely melted within 1 hour.
[0112] Freeze-thaw cycle: After 300 freeze-thaw cycles, the mass loss was only 1.2% (5.8% for ordinary concrete).
[0113] Chloride ion diffusion coefficient: 0.15 x 10-12 m 2 / s (50% reduction compared to the reference concrete).
[0114] Comparative Example 1
[0115] This comparative example provides a traditional uncoated deicing agent. The details include:
[0116] Components (parts by mass):
[0117] Composite salt (20 parts, ratio 1:1);
[0118] Zeolite powder (10 parts) activated at 130°C for 4 hours;
[0119] No coating material.
[0120] Performance test:
[0121] Freezing point: -27℃ (equivalent to Example 1).
[0122] Slow-release validity period: 1.5 years (85% of the initial Cl- release amount in the first year).
[0123] Cl- migration rate: 0.21 x 10-12 m 2 / s (162% higher than Example 1).
[0124] Carbonation depth: 2.0 mm in 56 days in a simulation environment of the Cross-Sea Bridge (67% higher than Example 2).
[0125] Compared with Examples 1-5 and Comparative Example 1, each example focuses on the proportion of composite salt, the type of porous carrier, the ratio of coating material, and the process parameters:
[0126] Example 1 uses a composite salt with a mass ratio of calcium magnesium acetate to sodium chloride of 1:1, and a single zeolite powder activated at 130℃ as the carrier (specific surface area 450 m 2 / g), the coating material is a mixture of sodium methyl silicate and phenolic resin at a ratio of 1:0.8 (2 parts), and the standard preparation process (vacuum adsorption, spray drying, etc. optimal parameters) is used.
[0127] Example 2 adjusts the proportion of composite salt to 1:0.5 (calcium magnesium acetate accounts for a higher proportion), and the carrier is replaced by diatomite activated at 120℃ (specific surface area 300 m 2 / g), the coating material accounts for 1.5 parts and the proportion of phenolic resin is reduced, focusing on the performance under low sodium chloride proportion.
[0128] Example 3 adjusts the proportion of composite salt to 1:1.5 (sodium chloride accounts for a higher proportion), and the carrier is selected as volcanic ash activated at 150℃ (specific surface area 600 m 2 / g), the coating material accounts for 3 parts and the proportion of phenolic resin is increased, to investigate the effects of high salt proportion and high coating amount.
[0129] Example 4 maintains the proportion of composite salt at 1:1, and uses a porous carrier mixed with zeolite powder and diatomite at a ratio of 7:3, to verify the improvement effect of different porous material compounding on adsorption stability.
[0130] Example 5 follows the optimal components of Example 1, and applies the anti-freezing agent to C50 concrete at a dosage of 3%, to test the actual application performance (such as freeze-thaw cycle, ice melting efficiency) in high-cold regions.
[0131] Comparative Example 1: The encapsulation layer was removed, and the rest of the components and process were consistent with Example 1, used to compare the key role of the encapsulation layer in slow release and corrosion resistance.
[0132] Comparison of core performance indicators
[0133] 1. Freezing point suppression and ice melting efficiency
[0134] Example 1: With a 1:1 composite salt ratio, the lowest eutectic system is formed, the freezing point is reduced to -28°C, which is 13°C lower than that of a single salt, and the ice melting rate is 0.8 g / cm 2 ·h, which is 45% higher than the comparative example (without encapsulation). This is because the encapsulation layer regulates the release rate of the salt, making the ice melting process more efficient and sustainable.
[0135] The freezing points of Example 2 (1:0.5) and Example 3 (1:1.5) are -25°C and -26°C, respectively. As the sodium chloride ratio deviates from 1:1, the freezing point decreases slowly, proving that 1:1 is the best eutectic ratio, which can balance the freezing point suppression and cost.
[0136] Slow-release performance and durability
[0137] Slow-release period: The slow-release periods of Examples 1-4 all exceed 2.5 years, among which Example 1 reaches 3.2 years (the salt release amount in the third year still reaches 70% of the initial value); while Comparative Example 1, without encapsulation, has a slow-release period of only 1.5 years (the release amount in the first year reaches 85%), directly reflecting the key role of the encapsulation layer in long-term slow release.
[0138] Cl- migration control: The Cl- migration rate of Examples 1-3 is reduced by 50%-62% compared to the comparative example, among which Example 3 with a 100 nm thick encapsulation layer performs best (migration rate 0.08 x 10-12 m 2 / s), proving that the denser the film layer, the stronger the inhibition effect on chloride ion penetration.
[0139] Freeze-thaw cycle and carbonation resistance: Example 5 has a mass loss of only 1.2% after 300 freeze-thaw cycles (ordinary concrete is 5.8%), and in the simulation environment of a cross-sea bridge, the carbonation depth is reduced by 40% compared to the comparative example, verifying that the encapsulation layer not only delays the release of salt, but also enhances the adhesion and carbonation resistance of the concrete matrix through hydrophobic interaction.
[0140] Synergistic effect of carrier and encapsulation
[0141] Porous carrier: Example 4 uses a mixed carrier of zeolite powder and diatomite, with a specific surface area of 420 m 2 / g, the adsorption capacity is increased by 15% compared with single zeolite powder, and the salt release rate only decreases by 10% after 100 cycles at-20℃ (decreases by 25% for single carrier), indicating that the combination of porous materials with different pore sizes can improve the adsorption stability through pore complementation, which is suitable for extreme environments.
[0142] Coating material: Comparative Example 1 does not add coating material, and the carbonization depth (2.0 mm) is increased by 67% compared with Example 2 (1.2 mm), and the Cl- migration rate is doubled, which directly proves that the hydrophobic film layer (contact angle ≥ 110°) formed by the combination of sodium methyl silicate and phenolic resin has the dual functions of physical barrier (slowing down salt loss) and chemical protection (chelating chloride ions).
[0143] Synergistic optimization of composite salt ratio: When calcium magnesium acetate and sodium chloride are compounded at a ratio of 1:1, the lowest freezing point and the most efficient ice melting system are formed through eutectic effect, and deviation from this ratio will lead to performance decline, verifying the rationality of the ratio range of 1:0.5-1.5 in the claim and the preferability of 1:1.
[0144] Irreplaceability of coating layer: The coating material controls the salt release rate (the slow-release period is extended by 1-2 times) and inhibits the migration of chloride ions (the rate is reduced by more than 50%), which solves the core problem of traditional anti-icing agents, i.e., severe corrosion and short service life, and is a key innovative point to realize the trinity of "anti-icing-corrosion-durability".
[0145] Adsorption-slow release mechanism of porous carrier: The activated zeolite powder, diatomite and other porous materials have high specific surface area (300-600 m 2 / g) and suitable pore size (2-5 nm), which can fix the composite salt through physical adsorption, and the coating layer cooperates to make the salt release more uniform and persistent, avoiding short-term massive loss.
[0146] After removing the coating material in the comparative example, although the freezing point suppression effect is similar, the slow-release period is shortened and the corrosion is intensified, which directly proves that the core creativity of the present application lies in the synergistic design of "composite salt-carrier-coating", rather than the improvement of single component.
[0147] Through the variable control experiment of 5 examples and the control of 1 comparative example, it is clearly shown that:
[0148] Component synergy: The ratio of composite salt, the type of porous carrier and the ratio of coating material interact with each other and jointly determine the core performance of the anti-icing agent, among which the combination of 1:1 composite salt ratio, zeolite powder carrier and methyl silicate-phenolic resin coating is the optimal scheme.
[0149] Process key: Vacuum adsorption (0.08-0.1 MPa) ensures the deep penetration of salt in the carrier pores, and spray drying (atomization pressure 10-15 MPa) guarantees the uniformity and density of the coating layer, which are indispensable.
[0150] The effect is progressive: from basic performance (freezing point, slow-release period) to application performance (freeze-thaw cycle, carbonation depth), each embodiment provides a repeatable experimental basis for the parameter range in the claims (such as the dosage of anti-freezing agent 3%-8%, anti-freezing grade F200 or above), fully proving the creativity, practicality and stability of the technical solution of the application.
[0151] The above embodiments can be realized wholly or partially by software, hardware, firmware or any other combination, and when realized by software, the above embodiments can be realized wholly or partially in the form of a computer program product.
[0152] Those skilled in the art can realize that the modules and algorithm steps of the examples described in combination with the embodiments disclosed herein can be realized by electronic hardware or a combination of computer software and electronic hardware, and whether the functions are realized in hardware or software depends on the specific application and design constraints of the technical solution, and a person skilled in the art can use different methods to realize the described functions for each specific application, but such implementation should not be considered beyond the scope of the present application.
[0153] In addition, the functional modules in each embodiment of the present application can be integrated in one processing module, or each module can exist physically alone, or two or more modules can be integrated in one module.
[0154] The above is merely a specific implementation of the present application, but the protection scope of the present application is not limited thereto, any person skilled in the art can easily think of changes or replacements within the technical scope disclosed in the present application, which should be included in the protection scope of the present application, therefore, the protection scope of the present application should be subject to the protection scope of the claims.
[0155] Finally: the above is only the preferred embodiment of the present application, and is not used to limit the present application, any modification, equivalent replacement, improvement, etc. within the spirit and principle of the present application should be included in the protection scope of the present application.
Claims
1. An anti-icing agent for concrete, characterized in that, The components include the following parts by weight: The complex salt consists of 10-30 parts, composed of calcium magnesium acetate and sodium chloride in a mass ratio of 1:0.5-1.5; 5-15 parts of porous carrier, consisting of zeolite powder activated at 120-150℃, with a specific surface area of 300-600 m². 2 / g, average pore size 2-5nm; The coating material consists of 1-3 parts, formed by free radical polymerization of sodium methylsilicate and phenolic resin at a mass ratio of 1:0.5-1.0, with a grafting rate of 30%-50% and a coating layer contact angle ≥110°. The composite salt lowers the freezing point to below -25°C through the eutectic effect, the porous carrier fixes the composite salt through physical adsorption, and the coating material forms a hydrophobic membrane through chemical bonding. The synergistic effect of the three reduces the migration rate of Cl- by more than 60%, and the sustained-release effect lasts for 3 years.
2. The anti-icing agent for concrete as described in claim 1, characterized in that, In the composite salt, the mass ratio of calcium magnesium acetate to sodium chloride is 1:1, at which point the freezing point drops to -28°C, and the melting rate is increased by 40% compared to the single salt.
3. The anti-icing agent for concrete as described in claim 1, characterized in that, The porous carrier also includes diatomaceous earth or volcanic ash activated at high temperature, with a specific surface area of 200-600 m². 2 / g, when mixed with zeolite powder, the total mass accounts for 30%-50% of the porous carrier.
4. The anti-icing agent for concrete as described in claim 1, characterized in that, The grafting rate of sodium methylsilicate in the coating material was detected by infrared spectroscopy and found to be in the range of 30%-50%, corresponding to a film thickness of 50-100 nm, which effectively inhibits the migration of salts in concrete pores.
5. A method for preparing an anti-icing agent for concrete, characterized in that, Includes the following steps: Step 1: Dry the zeolite powder at 120-150℃ for 4-6 hours to activate its pore structure; Step 2: Dissolve calcium magnesium acetate and sodium chloride in deionized water in a certain proportion to prepare a supersaturated solution. Mix the solution with the activated zeolite powder and adsorb it under a vacuum of 0.08-0.1 MPa for 2-3 hours. After drying, a salt-containing carrier is obtained. Step 3: Dissolve sodium methylsilicate and phenolic resin in ethanol, add ammonium persulfate as an initiator (0.5-1% of the monomer mass), and carry out free radical polymerization at 60-80℃ for 1-2 hours to form a coating precursor solution; Step 4: Disperse the salt-containing carrier in the coating precursor solution and form surface-coated anti-icing agent particles by spray drying (atomization pressure 10-15MPa).
6. The method for preparing an anti-icing agent for concrete as described in claim 5, characterized in that, In step 2, the temperature of the vacuum adsorption process is controlled at 40-50℃ to enhance the penetration depth of the composite salt in the pores of the zeolite powder.
7. The method for preparing an anti-icing agent for concrete as described in claim 5, characterized in that, In step 4, the inlet air temperature of the spray drying is 180-200℃, and the outlet air temperature is 80-100℃ to ensure the uniformity and stability of the coating layer.
8. The method for preparing an anti-icing agent for concrete as described in claim 5, characterized in that, The free radical polymerization reaction in step 3 is carried out under nitrogen protection to avoid oxidation side reactions affecting the performance of the coating material.
9. The method for preparing an anti-icing agent for concrete as described in claim 5, characterized in that, The thickness of the coating layer, as determined by scanning electron microscopy (SEM), is 50-100 nm, and the silicon content in the film layer, as shown by energy dispersive spectroscopy (EDS), is 15%-20%, corresponding to a sodium methylsilicate grafting density ≥0.8 molecules / nm. 2 .
10. The method for preparing an anti-icing agent for concrete as described in claim 5, characterized in that, In step 1, the activation degree of zeolite powder is determined by nitrogen adsorption. After activation, the micropore volume accounts for 60%-80% of the total pore volume, ensuring that the effective loading of the composite salt is ≥35% (mass fraction).